2013
DOI: 10.1016/j.meatsci.2012.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Surface-enhanced laser desorption/ionisation time-of-flight mass spectrometry: A tool to predict pork quality

Abstract: Expression of water soluble proteins of fresh pork Longissimus thoracis from 4 pure breed pigs (Duroc, Large White, Landrace, and Piétrain) was studied to identify candidate protein markers for meat quality. Surface-enhanced laser desorption/ionisation time-of-flight mass spectrometry (SELDI-TOF-MS) was used to obtain the soluble protein profiles of Longissimus thoracis muscles. The pure breeds showed differences among the studied meat quality traits (pHu, drip loss, androstenone, marbling, intramuscular fat, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…On the other hand, bottom up is a gel-free approach, where the proteins, after tryptic digestion, are separated based on chromatographic approach and subjected to mass spectrometry (LC-MS/MS). The identification/characterization of proteins in such methods could be made through isotope (ITRAQ; isobaric tags for relative and absolute quantitation, Aggarwal, Choe, & Lee, 2006) or chemical labeling, label free approach such as protein arrays (Lee & Nagamune, 2004), or SELDI-TOF (Surface-enhanced laser desorption/ionization; Marcos et al, 2013).…”
Section: Proteomic Approaches In Meat Quality Researchmentioning
confidence: 99%
“…On the other hand, bottom up is a gel-free approach, where the proteins, after tryptic digestion, are separated based on chromatographic approach and subjected to mass spectrometry (LC-MS/MS). The identification/characterization of proteins in such methods could be made through isotope (ITRAQ; isobaric tags for relative and absolute quantitation, Aggarwal, Choe, & Lee, 2006) or chemical labeling, label free approach such as protein arrays (Lee & Nagamune, 2004), or SELDI-TOF (Surface-enhanced laser desorption/ionization; Marcos et al, 2013).…”
Section: Proteomic Approaches In Meat Quality Researchmentioning
confidence: 99%
“…Unbound or non-specifically bound proteins are washed out to obtain only specific bound molecules. Finally, a chromatogram is generated using TOF-MS for identification ( 144 , 145 ). SELDI-TOF-MS enables the use of extremely small amounts of raw biological fluids and rapid screening of numerous biological samples simultaneously ( 146 ).…”
Section: Proteomics In Clinical Studiesmentioning
confidence: 99%
“…However, associations between protein peaks and meat quality traits, mainly colour (Minolta b * , meat yellowness) and texture (for details see Marcos et al, 2013a, b), were observed. Candidate protein markers for the quality of processed dry-cured hams were identified (Marcos et al, 2013b).…”
Section: Biomarkers For Resources For High-quality Dry-cured Ham Prodmentioning
confidence: 99%